The Effect of Quizizz Learning on the Interest in Science Study Class V SDN Wijaya Kusuma 01 West Jakarta City - Asfi Manzilah; Mujazi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study is on the background of the phenomena of a lack of interest in learning student science during the covid pandemic. As we can see during the industrial revolution of 4.0 this requires that all areas including education take advantage of the media technology in learning, but in reality there are teachers who still do not understand and apply the technology media well into learning. The purpose of this study is to know the impact of the use of quizizz learning media on the interest of studying science in Wijaya Kusuma 01 Pagi students class V B. The study is a quantitative study using survey methods. Population in this study of 32 respondents in class V B. a data collection technique on this study using questionnaire and documentation. Hypothetical results by using a partial test (t) obtained = 4,166 > = 2,042 with significant 0,000 < 0,05. The results showed that was rejected and accepted, which means that quizizz learning media variables positive impact on the interest of studying acience in Wijaya Kusuma 01 Pagi West Jakarta class V B